2015
DOI: 10.1007/s00586-015-3767-7
|View full text |Cite
|
Sign up to set email alerts
|

Posterior vertebral column resection in spinal deformity: a systematic review

Abstract: PVCR is a powerful surgical procedure for severe spinal deformity. However, it has the risk of excessive blood loss and major complications. Decision of PVCR should be prudent and the procedure should be performed by an experienced surgical team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 40 publications
3
81
2
6
Order By: Relevance
“…in this technique, the intraoperative estimated blood loss is generally around 3000-5000 mL, and the mean operative time is 9.3 h [16] . For spine deformity, PSO and VCR are classic techniques and can achieve satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…in this technique, the intraoperative estimated blood loss is generally around 3000-5000 mL, and the mean operative time is 9.3 h [16] . For spine deformity, PSO and VCR are classic techniques and can achieve satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] According to the results of the present study, correction rates of the main curve with PVCR were similar to those reported in previous studies of the technique. A systematic review of PVCR for correcting spinal deformity by Yang et al 41 reported a scoliosis correction rate of the main curve of 61.2%. Ozturk et al 30 reported a main scoliotic curve correction of 62% for PVCR in the treatment of patients with severe congenital kyphosis, scoliosis, or kyphoscoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Единственным способом радикальной коррекции тяжелого кифоза при запущенной врожденной деформации представляется VCR, предполагающая полное удаление позвонков на вершине кифотической дуги и последующее соединение верхнего и нижнего сегментов позвоночника металлоконструкцией [14,20,22]. Одномоментное значительное изменение геометрии позвоночного канала несет существенный риск: общая частота неврологических осложнений достигает 11,6 % [22], причем в некоторых сериях наблюдений исход в перманентную нижнюю параплегию составил 3 % [17]. Операция характеризуется большой ожидаемой кровопотерей [14,22] и высокой вероятностью несостоятельности металлоконструкции: 2,9 % больных в дальнейшем нуждаются в проведении ревизионных вмешательств [17].…”
Section: к линический с лу чайunclassified
“…Одномоментное значительное изменение геометрии позвоночного канала несет существенный риск: общая частота неврологических осложнений достигает 11,6 % [22], причем в некоторых сериях наблюдений исход в перманентную нижнюю параплегию составил 3 % [17]. Операция характеризуется большой ожидаемой кровопотерей [14,22] и высокой вероятностью несостоятельности металлоконструкции: 2,9 % больных в дальнейшем нуждаются в проведении ревизионных вмешательств [17]. Решение выполнить корригирующую вертебротомию у неврологически интактного пациента должно быть строго взвешенным и обоснованным.…”
Section: к линический с лу чайunclassified